2019
DOI: 10.5194/isprs-archives-xlii-2-w17-39-2019
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Terrestrial Lidar and Uav Photogrammetry for Interactive Architectural Heritage Visualization Using Unity 3d Game Engine

Abstract: Abstract. The digital 3D documentation of architectural heritage using advanced 3D measurement technologies such as UAV photogrammetry and terrestrial LiDAR (TLS) becomes a potential and efficient method since it can produce 3D pointclouds in detail and high density of pointclouds levels. However, TLS is unable to scan the roof part of tall building, whereas UAV photogrammetry achieves high density of pointclouds at that area. In order to make a complete 3D pointclouds of heritage building, we merged and integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The point cloud analysis comprises a defined XYZ value for every point, followed by an intensity value (due to the active source of the t-LiDAR method) or an RGB value (due to the passive source of the UAV method). This type of multi-vector analysis (sphere-by-sphere and point-by-point analysis) is currently a cuttingedge technology with significant potential in several geoscientific applications [119][120][121][122], while a combination of multi-source point clouds is feasible [123].…”
Section: Discussionmentioning
confidence: 99%
“…The point cloud analysis comprises a defined XYZ value for every point, followed by an intensity value (due to the active source of the t-LiDAR method) or an RGB value (due to the passive source of the UAV method). This type of multi-vector analysis (sphere-by-sphere and point-by-point analysis) is currently a cuttingedge technology with significant potential in several geoscientific applications [119][120][121][122], while a combination of multi-source point clouds is feasible [123].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, point clouds and UAV-SfM methods are the baseline for the production of 3D models for surface reconstruction, surface change detection, and soil erosion monitoring [44,82,83,115]. The 3D point-to-point analysis leads to high-accuracy results in several scientific applications regarding surface change detection [45,50,116,117]. This multi-vector analysis denotes the complexity of the microsurface, which cannot be accurately represented by 2.5D DEM data and the interpolation method [83].…”
Section: Discussionmentioning
confidence: 99%
“…(Buyuksalih et al, 2017) visualized 3D city models based on Unity3D and also estimated potential solar energy on buildings for Istanbul City. Other use cases are still limited and evolving, (Sihombing and Coors, 2018, Matthys et al, 2021, Edwards et al, 2015, Andaru et al, 2019 have already shown how 3D city models captured using geospatial technologies can be used with game engines for visualization of city objects, use of AR for city development, storytelling/public participation, AEC industry, preservation and visualization of heritage buildings. Such research shows the potential of 3D Unity visualization and game engine for 3D GIS visualization.…”
Section: State Of the Artmentioning
confidence: 99%